Transformasi Guru Agama Hindu SD di Kota Palangka Raya - Sri Pinatih, Ni Putu (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
The transformation of the role of Hindu religious education teachers at the elementary school level has become increasingly urgent in the face of 21st-century educational challenges. Teachers are no longer confined to the role of value instructors who merely deliver tattwa (philosophical teachings) and susila (ethics), but are also expected to serve as agents of character formation, internalizing the values of Dharma, Satya, Ksama, Ahimsa, Arjawa, and Daya in students’ daily lives. This study aims to analyze how Hindu religious education teachers in elementary schools are transforming from value transmitters into character agents, and to examine the implications for character education rooted in Hindu local wisdom. The research employed a qualitative descriptive approach through literature review and curriculum policy document analysis, complemented by contextual inquiry into classroom pedagogical practices. The findings indicate that Hindu religious education teachers in elementary schools, particularly in Palangka Raya, hold a strategic role in shaping the moral foundations of students at the concrete operational stage of development. The transformation of teachers’ roles is characterized by: (1) the application of Tri Kaya Parisudha values as a model of ethical conduct, (2) the integration of Hindu religious teachings with character education in elementary schools, and (3) the strengthening of teachers’ roles as role models capable of addressing the challenges of globalization and digitalization. This study highlights that Hindu religious education teachers at the elementary level are key figures in character education and support national education policies that position character education as a top priority.